BOOK REVIEW: Interesting-Unique Waqf in History - Fahimah, Rifah (Islamic Social Finance, 2025)
Books Tarihte İlginç Vakıflar (Interesting-Unique Waqf in History), published by Vakıflar Genel Müdürlüğü (Director General of Turkish Waqf) in January 2012 in Istanbul, Turkey. This book is the result of a collaborative study that highlights short stories, how the waqf institution system functions as a sustainable social policy by providing benefits in the fields of education, health and community welfare. Especially from the era of the Seljuk and Ottoman sultanates to be felt by modern society today. This book is packed with a simple story of daily life which aims to be a real illustration that waqf institutions can be applied to all aspects of life. Tarihte İlginç Vakıflar is a fascinating book in the study of Islamic social history, particularly regarding the unique and unusual practice of waqf (endowments) in the past. This book examines various types of waqf in the history of the Islamic world—especially the Ottoman Empire—which often sound "strange" but actually reflect a very high level of social civilization.